Strategi Employer Branding Perusahaan melalui Media Sosial Instagram @mncleasing.id: Studi Kasus pada PT MNC Guna Usaha Indonesia - Lintang Ayu Prasasti; Ike Oktaviani (Comit: Communication, Information and Technology Journal, 2026)
Competition in attracting and retaining top talent drives companies to build their image as preferred employers. In the digital era, social media particularly Instagram—has become a primary channel in employer branding strategies. This study analyzes the employer branding strategy of PT MNC Guna Usaha Indonesia (MNC Leasing) through its official Instagram account @mncleasing.id. This research employs a qualitative descriptive approach using content analysis of the company's Instagram posts during January–June 2024. A total of 763 posts were analyzed and categorized based on themes relevant to employer branding. The findings indicate that @mncleasing.id consistently applies five employer branding content categories: work culture, company values, achievements and awards, recruitment, and service information linked to employee professionalism. Findings are analyzed using Social Identity Theory (Tajfel & Turner, 1979) and Organizational Attractiveness (Lievens & Highhouse, 2003). This study concludes that the company builds its image as a professional, innovative, and dedicated workplace through consistent messaging and visual identity on Instagram.